Automated Technology for Verification and Analysis: 19th International Symposium, ATVA 2021, Gold Coast, QLD, Australia, October 18-22, 2021, Proceedings - Hou, Zhe; Ganesh, Vijay (Lecture Notes in Computer Science, 2021)
This book constitutes the refereed proceedings of the 19th International Symposium on Automated Technology for Verification and Analysis, ATVA 2021, held in Gold Coast, Australia in October 2021. The symposium is dedicated to promoting research in theoretical and practical aspects of automated analysis, verification and synthesis by providing an international venue for the researchers to present new results. The 19 regular papers presented together with 4 tool papers and 1 invited paper were carefully reviewed and selected from 75 submissions.The papers are divided into the following topical sub-headings: Automata Theory; Machine learning for Formal Methods; Theorem Proving and Tools; Model Checking; Probabilistic Analysis; Software and Hardware Verification; System Synthesis and Approximation; and Verification of Machine Learning.